Enter through the book shop: McLuhan monograffiti. Issue 9 (2nd September 2021) - McLuhan, Andrew
ABSTRACT: In the many conversations around or about Marshall McLuhan, what often gets lost or ignored is the fact that for his entire career he was an English professor: a teacher of literature and especially poetry. He came by it honestly, for his mother Elsie McLuhan was an elocutionist who performed dramatic monologues on stage, and although he began university in a mechanical engineering programme, during the summer between his first and second years he 'read himself into English' at night after long days as a rodman on a survey crew in the Manitoba north. Following that summer working in what cannot have been pleasant conditions, he left engineering for the arts programme at the University of Manitoba. It is hard to say whether he fell in love with literature or out of love with engineering – possibly it was a bit of both. Regardless, Marshall took a turn for the verse. Is the world better for it? Again, hard to say. Had his mind and energies been applied to the field of mechanical engineering for the following decades, who knows what contribution he would have made? What we can say with a fair degree of certainty is that had Marshall not majored in English Literature, he would not have learned the techniques of literary criticism that he eventually applied beyond literature to culture and technology – with world-changing results.